Comparison of the Effectiveness of Leaf Extracts of Anredera cordifolia, Psidium guajava and Pogostemon cablin on Inhibitory Power Over Escherichia coli Bacteria - Budianto, Budianto; Arum sari, Alif Gita; Inayah, Nurul; Fatmaningrum, F.; Suparmi, Anik (Vitae, 2021)
Background: the current research studies why it is effective using Anredera cordifolia, Psidium guajava, and Pogostemon cablin by the local community as a traditional medicine for diarrhea treatment caused by Escherichia colibacteria. Objectives: We compared the inhibitor effectiveness of three leaf extracts against Escherichia coli; we also identified the anti-bacterial substances contained in leaf extracts. Methods: We determined the bacterial test activity using the "agar diffusion" method and the thin layer chromatography (TLC) as qualitative analysis for determining the anti-bacterial substances contained in the extract. Results: The Pogostemon cablin leaf extract contained terpenoids, phenolic, and flavonoids compound as bacterial inhibitors, and the comparison showed that Pogostemon cablin leaf extract had the greatest bacterial inhibition power. Conclusion: The antibiotic substances found in the leaf extracts of Anredera cordifolia, Psidium guajava, and Pogostemon cablin can be used as traditional medicine. The breakthrough was evidenced by the ability to inhibit Escherichia coli bacteria. This research shows that traditional medicine has ancient knowledge used by this paper